Strategic management (GSTRAMA) - Pang Min Sin, Sharon (Animo Repository, 1999)
The objective of this paper is to provide a general application of the principles of strategic management to a real company situation. The industry chosen for the purpose of this paper is the Real Estate Industry. The company has agreed to be the subject of this paper on condition that is name is disguised. Hence, for the purpose of this paper the company shall be known as the Company. The Company is a private incorporated single business company engaged in the business of residential subdivision development. For the purpose of the subsequent industry and other analysis, we will adopt the working definition of an industry as the group of firms producing products that are close substitutes for each other. It is also assumed that the industry boundaries have already been drawn, that is, the development of a residential subdivision (hereinafter called the Industry). The initial focus of the strategic management process and the starting point of critical strategic thinsking are one of analysis. Hence, the external and internal environment analysis of the Company is necessary in order to match the strategy to the external and internal circumstances. The external environment analysis is divided into the Macro-Environment Analysis, Industry and Competitive Analysis and identifying the Companys external Opportunities and Threats. The internal environment involves the Companys external Opportunities and Threats. The internal environment involves the analysis of the situation of the Company and identifying its Strength and Weaknesses. The paper starts with the Macroenvironment Analysis followed by the Industry Competitive Analysis. The macroenvironment Analysis is divided into Social, Economic Political and Technological Environment. The Industry and Competitive Analysis is conducted by using techniques such as (a) Economic Characteristics of the Industry (b) Competition Analysis using the Five Forces Model (c) Driving Forces (d) Competitor Analysis (e) Key Success Factors and (f) Industry Prospect and Overall Attractiveness. Identifying the Companys Opportunities and Threats concludes the external environment analysis. The purpose of the identification of Opportunities and Threats is to enable the Company to match its Strength with its Opportunities and eliminate its Threats and Weaknesses. The next section of the paper involves probing into the internal environment of the Company by conducting a Company Situation Analysis. The techniques used in the paper for the Company Situation Analysis includes the Strategic Cost Analysis using the Company Value Chain, Identification of the Companys Strengths and Weaknesses and Competitive Strength Assessment. The subsequent section focuses on strategic choice, which involves the clarification of the Companys Vision and Mission statements including its Core Values from the Companys Objectives (strategic and financial) short and long-term can be derived. This is followed by the exploration of the Generic Strategy based on Michael Porters Competitive Strategy that the Company is pursuing in order to create a competitive advantage for itself. The Present Strategies of the Company by its different functional areas of Marketing, Operations, Human Resource and R&D are also probed to find out how well they are working and whether they need changes. The last under this section is the recommendation of any strategies both overall and by functional areas that need to be adjusted, reviewed or added. The Strategies Implementation section of the paper provides insights into the framework for the successful implementation of strategies. The Eight Big Managerial Components for the successful implementing of a strategy are generally discusses. These eight components are divided and discussed in two part, that is, Structure (Building a Capable Organization) and Policies (Budgets, Policies, Best Practices, Support Systems, Rewards, Culture and Leadership). The eight components essential for successful implementation of strategy are explained. It is also suggests the various steps involved in building a capable organization which involves probing into the organizational structure of the Company. The role of strategy supporting policies are surveyed and the last part deals with creating a strategy supportive culture and exercising the internal leadership needed to drive implementation forward. The paper concludes with a study of the financial projections.